A study of community mortality at the weekend versus during the week. Is there a correlation with in-hospital mortality?. Issue 4 (October 2019) - Beaumont, Oliver; Willett, Matthew; Dutton, Susan; Vadher, Karen
Abstract: Objective: A so-called 'weekend effect' has been described in which mortality among those admitted to hospital at a weekend is higher than among those admitted on weekdays. The causes for the weekend effect remain unclear. This study examined patterns of community mortality to explore whether a shift from the community to hospital may account for observed differences in hospital mortality rates across the week. Methods: The annual number of deaths in the community was compared to that in hospitals in England and Wales during 2012 to 2014 using data from the Office for National Statistics. Analyses included the mean annual deaths, by age group and by cause of death in the community and hospital and comparison of the proportion of deaths on each day of the week to the expected number of deaths. Results: The observed and expected total number of deaths in the community were broadly similar on the weekend and weekday ( P = 0.386). There was no difference between observed and expected rates when comparing average daily weekday deaths to the average daily weekend deaths in the community ( P = 0.434). In addition, there was no difference in the proportion of deaths in the community on the weekend when compared to the expected rate for those aged under 65, 75–84 and 85+ years. People were more likely to die on the weekend (rather than the weekday) in the community from neoplasms ( P = 0.009) but less likely to die from cardiovascular disease ( P = 0.012) or those aged 65–74 years. Conclusion: We found no evidence of a significant difference in the risk of dying in the community at the weekend compared to during the week, or between the observed and expected deaths on each day. The lower risk of dying in the community at the weekend from cardiovascular diseases and among those aged 65–74 years and the higher risk for neoplasms are of interest but marginal. We found no evidence of a shift in deaths from the community to hospital at weekends.